Profiling the expression domains of a rice-specific microRNA under stress - Sharma, Neha; Tripathi, Anita; Sanan-Mishra, Neeti (Frontiers in Plant Science, 2015)
Plant microRNAs (miRs) have emerged as important regulators of gene expression under normal as well as stressful environments. Rice is an important cereal crop whose productivity is compromised due to various abiotic stress factors such as salt, heat and drought. In the present study, we have investigated the role of rice-specific Osa-miR820, in indica rice cultivars showing contrasting response to salt stress. The dissection of expression patterns indicated that the miR is present in all the tissues but is enriched in the anther tissues. In salinity, the miR levels are up-regulated in the leaf tissues but down-regulated in the root tissues. To map the deregulation under salt stress comprehensive time kinetics of expression was performed in the leaf and root tissues. The reproductive stages were also analyzed under salt stress. It emerged that a common regulatory scheme for Osa-miR820 expression is present in the salt-susceptible Pusa Basmati 1 (PB1) and salt-tolerant Pokkali (PK) varieties, although there is a variation in the levels of the miR and its target transcript, OsDRM2. The regulation of Osa-miR820 and its target were also studied under other abiotic stresses. This study thus captures the window for the miR-target correlation and the putative role of this regulation is discussed.This will help in gaining useful insights on the role of species specific miRs in plant development and abiotic stress response.